ANALYSIS OF SOUND PRESSURE LEVEL (SPL) AND LAY OUT OF ENGINES IN THE FACTORY - Wijianto Wijianto (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2007)
Modeling layout of engines in the factory is very useful to know how many dB sound pressure level that are occur in the building in order to avoid hearing damage of employees that are caused by noise. The objective of this research is to know how many dB sound pressure level that are occur in the factory with engine composition such as boiler, diesel, turbine, motor and gear box with dimension of building are 40 m length, 35 m width and 10 m height. With MATLAB analysis can be obtain that the highest SPL is 104.7 dB and the lowest is 93.5 dB, so, this range are dangerous for human hearing. To avoid hearing damage in this area, employees must use hearing protector.